"My Musical Armor": Exploring Metalhead Identity through the Battle Jacket. Issue 1 (2nd January 2022) - O'Hagan, Lauren Alex
ABSTRACT: This paper offers the first detailed exploration of the key functions and meanings of battle jackets – sleeveless denim jackets customized with band patches – for heavy metal fans. Drawing upon a dataset of 50 battle jackets collected from Instagram and Reddit, coupled with evidence from questionnaires and comment threads, it identifies three key aspects of battle jackets (sense of community, pursuit of selfhood, and codes of civility/authenticity) that turn it into a cultural biography that is central to a person's sense of identity and web of memories. It argues that battle jackets should be reconsidered as sophisticated and multifaceted artifacts that have a range of important sociocultural functions embedded in a rich history.